Efficient evaluation of optical quantum modules via two-photon high-dimensional interference - Xiaoqian Zhang; Maolin Luo; Xiaoqi Zhou (Proceedings of the National Academy of Sciences, 2026)
The rapid advancement of quantum information technology has increased the demand for precise testing and calibration of quantum modules, especially in optical quantum circuits where module reliability directly impacts system performance. To address this need, we propose a two-photon quantum module evaluation method based on high-dimensional Hong–Ou–Mandel interference. Our method uses multi-degree-of-freedom photon encoding to enable rapid and accurate evaluation of optical quantum modules. Compared to traditional methods such as quantum process tomography and direct fidelity estimation, our method not only simplifies implementation but also significantly minimizes the measurement resources required. Notably, the resource demands remain invariant as the system dimensionality scales, ensuring efficient evaluation even in high-dimensional quantum systems. We validated this method on a programmable silicon photonic chip, demonstrating its ability to accurately evaluate optical quantum module performance while significantly reducing resource consumption. This quantum module evaluation method holds promise for broader applications in the field of optical quantum information technologies.